Exploring the Relationship between Working Capital Management, Profitability and Capital Structure - Abdussalam, Abdalla Geth; Mohd Ridzuan, Darun (Global Academy of Training & Research (GATR) Enterprise, 2017)
Objective – This paper explores the relationship between working capital management (WCM), profitability and capital structure. A preliminary framework provides an understanding of the role of WCM components with capital structure and profitability. Methodology/Technique – From the review of empirical studies it is confirmed that WCM is a main component in the financial aspects of the firms as even though WCM is targeted for the short-term decisions it has effect on the firm for the long-run. Findings – Companies need to use working capital policy and procedures in order to navigate performance. Emphasizing on WCM would lead to formal cost controls and performance together with firm’s growth and productivity. The framework is set to help financial manager of the firms to balance the costs and benefits of debt and equity and reduce common obstacles on managing cash flows for long-term fixed investment. Novelty – The preliminary framework is original and unique that will contribute towards the enrichment of relevant literature. Practically, this study contributes to provide a better understanding of the managers and enable them to apply WCM strategies and make sure the firm is able to meet the stakeholder requirements.